PERAN TENAGA ADMINISTRASI DALAM MENINGKATKAN MUTU LAYANAN ADMINISTRASI DI MTs. HIDAYATUL MUHSININ - Abdul Pandi (Mudir : Jurnal Manajemen Pendidikan, 2022)
Researchers are interested in researching this in order to find out: The Role of Administrative Personnel in Improving the Quality of Administrative Services at Mts. Hidayatul Muhsinin With the main problem: Activities and Role of Administrative Personnel in Improving Service Quality, Barriers in Improving Administrative Service Quality and Strategies in Improving Administrative Service Quality. The method used in this study is a descriptive method with a qualitative approach. The main data sources in this study were school principals, Deputy Head of Curriculum, Finance Head of Administration and teachers obtained through interviews, observation, and documentation. The results of this study indicate that 1). The performance of administrative staff with the strategy implemented is to facilitate the payment or fee system that has been implemented since 2008, and maintain and manage school infrastructure facilities. The integration of the program from administrative staff with daily activities at school is still ongoing, although there are several obstacles in implementation. 2). The obstacles faced by schools in managing administrative services are archive warehouses that have not been optimal, a comprehensive database system has not been implemented and the preparation of the School Revenue and Expenditure Budget Plan still has difficulties related to costs that are not raised, existing facilities still have complaints from service users but complaints These complaints are not always handled quickly because they are related to the number of administrative staff. 3). Efforts are being made to overcome some of these obstacles, namely providing a letter of notification to parents to collect files immediately, increasing the payment of school fees to new students to cover the financing system that is not increased, so that each class pays school fees with different fees, the next strategy implementation of a system for controlling the condition of school facilities. The most important aspect that determines the success of an educational institution is the efficient implementation of all school organizational activities. The role of the administrative staff themselves in the school is very meaningful in supporting the smooth and successful administration of the school. Therefore, the administration must be able to carry out its duties and functions properly so that competence and expertise are needed to support the field of administration.